A=p+prt, for t

how about subtracting p from both sides, then dividing both sides by pr

I think it could be A divided by p, then the quotient of that minus the product of r and t.

if you divide by p first you get

A/p = 1 + rt

then A/p - 1 = rt
now you still have to divide by r
(A/p - 1)/r = t looks pretty messy

the way I had suggested:
A-p = prt
(A-p)/(pr) = t

Sorry, I don't have a clue what I was talking about, I'm just waiting around for my questions to be answered and looking at the other posts. don't mind me:')

  1. 👍 0
  2. 👎 0
  3. 👁 141
asked by alexia

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math2(Please help)

    Directions:Solve and explain the inequality using words.Tell which wa shading goes. Problem: x+3=>2x+1 and -4x

    asked by margie on April 10, 2007
  2. Math

    Jerome claims he can find the area of the composite shape shown by inscribing it in a rectangle and subtracting. Kelly claims that to find the area you need to use addition. Who is correct? Justify your answer.The picture looks

    asked by Ann on May 16, 2015
  3. Math[Please Help]

    Solve the inequality x > 6x - 10 and write a description of the graph. Show all work Subtracting x from both sides does not change the inequality sign direction. 0 > 5x - 10 Add 10 to both sides 5x < 10 Divide both sides by 5. x <

    asked by Margie on February 24, 2007
  4. algebra

    how do I do this Solve for x. 3x – 2y = 6 Add 2y to both sides and then divide both sides by 3, to give you just "x' on the left side. so is this how i work it out 3x-2y=6 3x- 2y= 6 -2y 3x=6-2y x= 2 +2y No. Add 2y to both sides.

    asked by help on April 28, 2007
  5. math,help

    can someone help me with this i am lost now i've been doing math for the past 8 hrs. Problem # 1 solve: 4(x-10)-3x=x-40 Problem # 2 solve for t: a = p + prt Problem#3 translate to an algebraic equation 7 less than the quotient of

    asked by jasort20 on March 18, 2007
  6. Math

    If 4X + Y =H, Then X is equal to? 4X + Y =H Move Y to other side by subtracting Y from both sides. 4X + Y - Y = H - Y Combine terms. 4X = H - Y Now divide both sides by 4 to get 1X. 4X/4 = (H - Y)/4 X = (H-Y)4 or (1/4)(H-Y)

    asked by Pam on April 16, 2007
  7. pre-algebra

    x+5/4=3/4x The next step would be obtained by subtracting 3/4 x + 5/4 from both sides. That gives yoju x/4 = -5/4 Now multiply both sides of the equation by 4.

    asked by Geri on March 13, 2007
  8. maths

    6y=9-3x rearrange for x= Change 6y = 9 - 3x to: 3x = -6y + 9, then solve for x by dividing both sides by 3 to get: x = -2y + 3 when you divided both sides by 3. there is a rule where you cant divide the answer if theirs an

    asked by forest on May 8, 2007
  9. Math

    How can just adding one or subtracting one make the difference? I did the first one but can't come up with the second one. The first equation is: x = 4y + 1 Subtract 1 from both sides x - 1 = 4y Now divide both sides by 4 (x/4) -

    asked by Emily on June 3, 2014
  10. dividing a polynomial by a polynomial

    (-6v^2 - 4 + 9v +v^3)/ (v - 4)i am just a little lost can someone explain this to me. thanks. Arrange the polonomial in descending order... v^3-6v^2 +9v -4 Then divide. v-4 !v^3-6v^2 +9v -4 The first term is v^2, so v^2*(v-4) is

    asked by Angel007 on August 1, 2005

More Similar Questions